Tunable shape memory behavior of polymer with surface modification of nanoparticles - Biswas A.; Aswal V.K.; Maiti P. (My University, 2025)
In-situ inclusion of different nanoclays during synthesis results in different level of dispersion of nanoclays in the polymer matrix depending upon the surface modification of the nanoclay. Higher intercalation of the polymer chains within the galleries of organically modified nanoclay results better dispersion as compared to pristine nanoclay. The spectroscopic measurement shows that the extent of interaction between the nanoclay and polymer chains is higher in modified nanoclay nanocomposite which decreases the crystallinity considerably as compared to pristine clay nanocomposite. Interestingly, shape memory behavior measured at physiological temperature (37 °C) improves significantly in presence of organically modified nanoclay while it decreases in presence of unmodified nanoclay in same polyurethane matrix. Complete melting of soft segment along with restricted flipping of hard segment with temperature in presence of extensive interaction in nanocomposite with modified nanoclay helps it to achieve better shape memory behavior against flipping induced stacking of hard segment with temperature along with poor interaction decreases its shape memory behavior in nanocomposite with unmodified nanoclay. Temperature dependent nanostructure reveals the cause of variation in shape memory behavior in presence of organically modified nanoclay. Further, the cell culture studies like cell adhesion, cell viability assay and fluorescence imaging, suggest superior biomaterial of the nanocomposite with modified nanoclay as compared to other composite. Better biodegradable nature of the modified nanocomposite makes it suitable candidate for its potential biomedical applications. © 2019 Elsevier Inc.